The Effectiveness of Predict-Observe-Explain (POE) Model in Enhancing Students' Critical Thinking Skills on Colloid Topic - Sihite, Meri Septiani; Asri, Zakiyah; Ali, Syeh Chasina; Yasthophi, Arif; Kurniawati, Yenni (PendIPA Journal of Science Education, 2026)
Cultivating critical thinking skills in colloidal subjects is difficult due to the intricacy of abstract concepts, even though they are pertinent to daily life. This study seeks to evaluate the efficacy of the Predict-Observe-Explain (POE) learning model in improving high school students' critical thinking skills in colloid science. This pre-experimental study employed a one-group pretest-posttest design with 36 11th-grade science students chosen via purposive sampling. The research instrument comprised an essay test formulated according to Facione’s critical thinking indicators. The findings demonstrated a substantial enhancement in students’ average scores, rising from 32.55 to 75.14, accompanied by a Normalized Gain (N-gain) of 0.635 (moderate). An analysis based on indicators showed that the POE model was best at helping students improve their deduction and inference skills, but it still needed work on helping them figure out how trustworthy information sources are. This study concludes that the POE model is effective in enhancing scientific argumentation; however, it necessitates supplementary scaffolding to fortify students' metacognitive skills in the validation of external information.